Early Detection of Maternal Risk Factors for Stunting in Infants - Iin Setiawati; Selvia Nurul Qomari; Dana Daniati (Jurnal Keperawatan Soedirman, 2026)
Stunting can develop while fetus is still in womb and is only visible in infants at two years of age. Indonesia’s stunting rate reached 19.8% in 2024, which is still higher than government's target of below 14%. This study aims to identify maternal risk factors for stunting. This retrospective study applied a quantitative analysis approach. A total of 323 mothers participated in this study, and researchers used Early Detection of Low-Birth-Weight Risk Scorecard (EDBLWRSC) and Dhiana Setyorini Scorecard (DSSC) to collect data. The analyzed using Chi-square tests with an α of 0.05. The results revealed that stunting was associated with parity item of DSSC (ρ = 0.00) and a history of preeclampsia (ρ = 0.00). Meanwhile, obesity was associated with either outcome. Moreover, in EDBLWRSC, anemia was associated with stunting (ρ = 0.00), a history of low birth weight was associated with a higher incidence of low birth weight (ρ = 0.01). The maternal risk variable on DSSC and stunting (ρ = 0.00) had an OR of 2.2 and 3.3, respectively. The EDBLWRSC also revealed a relationship between maternal risk factors and stunting (ρ = 0.00). Therefore, some of maternal risk factors in DSSC and EDBLWRSC are associated with stunting.